Iterative Detection and Decoding Algorithms for MIMO Systems in Block-Fading Channels Using LDPC Codes - Uchoa, Andre G. D.; Healy, Cornelius T.; de Lamare, Rodrigo C. (IEEE transactions on vehicular technology, 2016)
We propose iterative detection and decoding (IDD) algorithms with low-density parity-check (LDPC) codes for multiple-input multiple-output (MIMO) systems operating in block-fading and fast Rayleigh fading channels. Soft-input-soft-output minimum-mean-square-error (MMSE) receivers with successive interference cancellation are considered. In particular, we devise a novel strategy to improve the bit error rate (BER) performance of IDD schemes, which takes into account the soft a posteriori output of the decoder in a block-fading channel when root-check LDPC codes are used. A MIMO IDD receiver with soft information processing that exploits the code structure and the behavior of the log-likelihood ratios is also developed. Moreover, we present a scheduling algorithm for decoding LDPC codes in block-fading channels. Simulations show that the proposed techniques result in significant gains in terms of BER for both block-fading and fast-fading channels.